Core/Shell ZnO/TiO2, SiO2/TiO2, Al2O3/TiO2, and Al1.9Co0.1O3/TiO2 Nanoparticles for the Photodecomposition of Brilliant Blue E-4BA - Mahboubeh Dolatyari; Mehdi Tahmasebi; Sudabeh Dolatyari; Ali Rostami; Armin Zarghami; Ashish Yadav; Axel Klein (Inorganics)
The synthesis and characterization of ZnO/TiO2, SiO2/TiO2, Al2O3/TiO2, and Al1.9Co0.1O3/TiO2 core/shell nanoparticles (NPs) is reported. The NPs were used for photocatalytic degradation of brilliant blue E-4BA under UV and visible light irradiation, monitored by high-performance liquid chromatography and UV-vis absorption spectroscopy. The size of the NPs ranged from 10 to 30 nm for the core and an additional 3 nm for the TiO2 shell. Al2O3/TiO2 and Al1.9Co0.1O3/TiO2 showed superior degradation under UV and visible light compared to ZnO/TiO2 and SiO2/TiO2 with complete photodecomposition of 20 ppm dye in 20 min using a 10 mg/100 mL photocatalyst. The “Co-doped” Al1.9Co0.1O3/TiO2 NPs show the best performance under visible light irradiation, which is due to increased absorption in the visible range. DFT-calculated band structure calculations confirm the generation of additional electronic levels in the band gap of γ-Al2O3 through Co3+ ions. This indicates that Co-doping enhances the generation of electron–hole pairs after visible light irradiation.